The genome and GeneBank genomics of allotetraploid Nicotiana tabacum provide insights into genome evolution and complex trait regulation - Zan, Yanjun; Chen, Shuai; Ren, Min; Liu, Guoxiang; Liu, Yutong; Han, Yu; Dong, Yang; Zhang, Yao; Si, Huan; Liu, Zhengwen; Liu, Dan; Zhang, Xingwei; et al. (Springer, 2025)
Nicotiana tabacum is an allotetraploid hybrid of Nicotiana sylvestris and Nicotiana tomentosiformis and a model organism in genetics. However, features of subgenome evolution, expression coordination, genetic diversity and complex traits regulation of N. tabacum remain unresolved. Here we present chromosome-scale assemblies for all three species, and genotype and phenotypic data for 5,196 N. tabacum germplasms. Chromosome rearrangements and epigenetic modifications are associated with genome evolution and expression coordination following polyploidization. Two subgenomes and genes biased toward one subgenome contributed unevenly to complex trait variation. Using 178 marker–trait associations, a reference genotype-to-phenotype map was built for 39 morphological, developmental and disease resistance traits, and a novel gene regulating leaf width was validated. Signatures of positive and polygenic selection during the process of selective breeding were detected. Our study provides insights into genome evolution, complex traits regulation in allotetraploid N. tabacum and the use of GeneBank-scale resources for advancing genetic and genomic research.